Incidence and characteristics of early elevation of cardiac troponin I after intrathoracic surgery: A single-center retrospective observational study. Issue 13 (31st March 2023) - Nandate, Hideyuki; Takasaki, Yasushi; Nakata, Yukihiro; Hamada, Taisuke; Konishi, Amane; Abe, Naoki; Kitamura, Sakiko; Nishihara, Tasuku; Yorozuya, Toshihiro
Abstract : The early elevation of cardiac troponins within 24 hours after noncardiac surgery is reportedly associated with increased postoperative morbidities. Several predisposing factors, including the frequent occurrence of hypoxia and increased pulmonary arterial pressure, may likely contribute to this elevation, especially after intrathoracic surgery. Therefore, this retrospective study aimed to elucidate the incidence and characteristics of the early elevation of cardiac troponin I after intrathoracic surgery. This study included 320 patients who underwent intrathoracic surgery between January 1, 2018, and June 30, 2021. Specific perioperative variables were retrospectively collected from their electrical clinical records. The serum concentration of high-sensitivity cardiac troponin I (hs cTnI) was measured twice immediately after the intensive care unit arrival and on the following day. We grouped these patients into two: the early elevation of hs cTnI (EECT) group (hs cTnI value > 26.2 ng/L by at least 1 measurement) and the non-early elevation (non-EECT) group. Patient characteristics were then compared between these groups. The hs cTnI level elevated within 24 hours postoperatively in 103 patients (32.2%). In univariate analysis, intraoperative variables, including the duration of unilateral ventilation (199.2 minutes, P = .0025) and surgery (210.6 minutes, P = .0012), estimated blood loss volume (406.7 mL, P = .0022), percentage of stored red blood cell (RBC) transfusion (10.7%, P = .0059), and percentage of lobectomy or combination of other lung resection types (88.3%, P = .00188), were significantly higher in the EECT group than in the non-EECT group. In the log-rank test, prolonged hospitalization was more prevalent in the EECT group ( P = .0485). Furthermore, multivariate analysis revealed 3 independent risk factors for the early elevation of hs cTnI: coexisting chronic renal failure (odds ratio [OR], 3.25), lobectomy or combined resections (OR, 2.65), and stored RBC transfusion (OR, 3.41). The early elevation of hs cTnI commonly occurs after intrathoracic surgery, with an incidence of 32.2%. Its 3 independent risk factors are coexisting chronic renal failure, lung resection type, and stored RBC transfusion.